Mathematical Reasoning Ability On PACE Learning Model assisted by Ispring - Fadlurreja, Robbi; Ridlo, Saiful; Dewi (Nino Adhi), Nuriana Rachmani (Unnes Journal of Mathematics Education Research, 2020)
This study aims to (1) analyze the effectiveness of the PACE learning model assisted by Ispring media on students' mathematical reasoning ability; (2) describe the pattern of students' mathematical reasoning on the PACE learning model assisted by Ispring media. The method was mixed method with embedded concurrent design. The population in this study were eighth grade students of SMP Negeri 2 Cilimus 2018/2019 and the sample were two selected classes namely VIII F and VIII G. Quantitative data collection was done by mathematical reasoning ability tests and students’ worksheets, While the qualitative data was done by the results of testing mathematical reasoning ability. The results of the mathematical reasoning ability test were analyzed to know the effectiveness of mathematics learning by using individual completeness test, classical completeness test, influence test, and achievement test. Students are grouped based on groups I, II, and III, which each of them got the scores 80-87, 73-79, and 68-72. The results of the study were (1) the PACE learning model assisted by Ispring media was effective; (2) the students in Group I were able to change the problems into a mathematics model, there was no difficulty in connecting mathematical situations, were able to compile evidence directly and then explain although there were still difficulties in connecting mathematical situations, and were able to compile evidence directly, and examine arguments to provide an explanation even though there were still shortcomings. The students in Group II have not been able to convert real problems into mathematical form, but were able to connect mathematical situations and compile evidence directly, were able to explain arguments quickly and precisely even though there were still some difficulties. The students in Group III were able to change it into the mathematical model, the students in this group still faced difficulties.